Planning for tourism based development : a case of Govardhan Parikrama Marg, Uttar Pradesh - Purwar, Devarshi (SPA Bhopal, 2020)
In India, religious tourism is the tourism, when the individuals make visits to different places for religious purposes. The individuals possess strong religious beliefs and form the viewpoint that religious tourism would promote their well-being. Tourists usually visit in the Braj region to perform parikramas (circuits) linking major religious places around the region. There is a sacred destination located in the district of Mathura in Uttar Pradesh - Govardhan Parvat, a hill which is believed to be lifted by Lord Krishna on his finger. Devotees from round the world come to this place every day to do the parikrama of the hill. This entire Govardhan Parikrama is about 21 km which takes around 5-6 hours to complete. In route to this highly sacred pilgrimage in Uttar Pradesh, several important holy sites are also covered, Including Radha Kund, Shyama Kund, Daan-Ghati Mandir, Mukharvind, Kusuma Sarovar, Rinamochana, and Puchari. The Parikrama Path goes through various Land use like residential areas, commercial spaces, Transportation paths, riverbeds etc. The aim of this study is to examine the perceptions of tourists visiting the town of Govardhan with regard to the importance given to and the satisfaction level with respect to the infrastructure, facilities, services and amenities available for tourism; to identify infrastructural strengths as well as problem areas which will enable various stakeholders to take appropriate measures. On the Govardhan Parikrama Marg even the peak population on festivals like Guru Purnima, Govardhan Puja and Janmashtami sometimes rises to as high as 10 lakhs. However, is observed a dire lack of basic tourism infrastructure, though Govardhan is a pilgrim and tourist intensive town. There are also challenges related to inadequate boarding and lodging accommodation facilities for various economic classes. The Govardhan Parikrama Marg is a circumambulating path around the town. Devotees walk barefoot along this Parikrama Marg especially on festive seasons. However, it lacks an integrated functional character to develop unify the entire stretch. It needs an augmentation of pilgrim facilities. Infrastructure development requires that religious tourism circuits be identified, and StateGovernment is required to streamline the development of the entire religious tourism circuit existing in each region/area. The study area is centred around the Parikrama Marg. The study is expected to provide a broader and improved experience to tourists visiting one of the most important destinations in the Parikrama Marg. while upgrading the infrastructure and services to improve living conditions for its residents
Keywords: B. Plan 2016; Govardhan Parikrama Marg, Uttar Pradesh; Religious tourism; Religious tourism development-Govardhan Parikrama Marg, Uttar Pradesh